2015
DOI: 10.5114/ceji.2015.54590
|View full text |Cite
|
Sign up to set email alerts
|

Humoral responses of broiler chickens challenged with NDV following supplemental treatment with extracts of Aloe vera , Alma millsoni , Ganoderma lucidum and Archachatina marginata

Abstract: Aim of the studyThe significance of nutritional supplements for immunity has been documented. Locally sourced extracts used in alternative medicine were studied to determine their potential effects on antibody production and humoral responses in viral challenged birds.MethodThree hundred and eighty birds were distributed into 19 groups of 20 birds each. Following acclimatization for 16 days, they were fed with standard broilers feed and water ad libitum. Group A was supplemented with Aloe vera (AV) extract, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…3 ). Therefore, the influence of the tested herbal extracts on humoral immunity could not be confirmed despite the fact an increase in the percentage of anti-NDV antibodies after the administration of Aloe vera extract has been reported by other authors [ 26 ]. However, in a study of rabbits, the Aloe vera extract did not influence serum immunoglobulin levels [ 43 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…3 ). Therefore, the influence of the tested herbal extracts on humoral immunity could not be confirmed despite the fact an increase in the percentage of anti-NDV antibodies after the administration of Aloe vera extract has been reported by other authors [ 26 ]. However, in a study of rabbits, the Aloe vera extract did not influence serum immunoglobulin levels [ 43 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 78%
“…Vahedi et al (2011) reported a higher percentage of CD4 + and CD8 + T cells in the peripheral blood of rabbits receiving Aloe vera extract [ 43 ]. Aloe vera extracts were also found to stimulate humoral immunity in chickens experimentally infected with the Newcastle disease virus (NDV) [ 26 ]. The discussed plant delivers numerous health benefits and exerts anti-inflammatory, antibacterial, antifungal and anti-carcinogenic effects due to the presence of anthraquinones, saccharides and antioxidant vitamins (A, C and E) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ReishiMax suppressed expression of enzymes and proteins responsible for lipid synthesis, transport and storage: fatty acid synthase (FAS), acyl-CoA synthetase-1 (ACS1), fatty acid binding protein-4 (FABP4), fatty acid transport protein-1 (FATP1) and perilipin, Further RM induced, AMP-activated protein kinase (AMPK) and increased glucose uptake in 3T3-L1 cells by adipocytes. Ganoderma lucidum extracts enhanced the ability to mount humoral responses against viral infection in broiler chickens (Ojiezeh & Eghafona 2015). Chu et al (2007) reported G. lucidum aqueous extract (GLE) on sleep and its sedative activity in a rat model.…”
Section: Other Beneficial Properties Of Ganoderma Lucidummentioning
confidence: 99%
“…To date, the efficacy of aloe vera and licorice extracts against paramyxovirus infections has been studied only in chickens based on the results of standard laboratory tests evaluating blood biochemical parameters, weight gains, and antibody levels against NDV (Waihenya et al, 2002 ; Ojiezeh and Eghafona, 2015 ; Ojiezeh and Ophori, 2015 ).…”
Section: Introductionmentioning
confidence: 99%